Fetal bovine serum is associated with polar body degeneration after in vitro maturation of bovine oocytes - MACÍAS-GARCÍA, B.; MACEDO, S.; ROCHA, A.; GONZÁLEZ-FERNÁNDEZ, L. (Journal of the Hellenic Veterinary Medical Society, 2018)
In vitro fertilization (IVF) in cattle is commonly used worldwide. Although extensive research has been conducted using different additives in the different IVF steps, little is known regarding how protein type may affect bovine oocytes during the fertilization period. In addition, unlike Tissue Culture Medium 199 (TCM), fertilization medium may induce oocytes’ chromatin degeneration during prolonged incubation in the horse (Modified Whitten’s medium). Thus, in the present work TCM-199 supplemented with either 7 mg/ml of Bovine Serum Albumin (TCM+BSA) or 10% Fetal Bovine Serum (v/v; TCM+FBS) was used. Bovine oocytes were matured in vitro and placed in the previously mentioned media for further 18 hours, in the absence of added sperm (sham fertilization) and their chromatin conformation was evaluated. After IVM, 78.9% of the initial oocytes had reached the MII stage. After sham fertilization, 58.6% of the oocytes in TCM+BSA while just 28.3% in TCM+FBS maintained the MII chromatin conformation (p < 0.05). Subsequent experiments run using PB extruded oocytes and incubated in TCM+BSA and TCM+FBS during sham fertilization, demonstrated that FBS was consistently associated with polar body dissolution or degeneration.